Loss of RANKL in osteocytes dramatically increases cancellous bone mass in the osteogenesis imperfecta mouse (oim) - Zimmerman, Sarah M. (Bone Rep, 2018)
Osteogenesis imperfecta (OI) is characterized by osteopenia and bone fragility, and OI patients during growth often exhibit high bone turnover with the net result of low bone mass. Recent evidence shows that osteocytes significantly affect bone remodeling under physiological and pathological conditions through production of osteoclastogenic cytokines. The receptor activator of nuclear factor kappa-B ligand (RANKL) produced by osteocytes for example, is a critical mediator of bone loss caused by ovariectomy, low-calcium diet, unloading and glucocorticoid treatment. Because OI bone has increased density of osteocytes and these cells are embedded in matrix with abnormal type I collagen, we hypothesized that osteocyte-derived RANKL contributes to the OI bone phenotype. In this study, the conditional loss of RANKL in osteocytes in oim/oim mice (oim-RANKL-cKO) resulted in dramatically increased cancellous bone mass in both the femur and lumbar spine compared to oim/oim mice. Bone cortical thickness increased significantly only in spine but ultimate bone strength in the long bone and spine was minimally improved in oim-RANKL-cKO mice compared to oim/oim mice. Furthermore, unlike previous findings, we report that oim/oim mice do not exhibit high bone turnover suggesting that their low bone mass is likely due to defective bone formation and not increased bone resorption. The loss of osteocyte-derived RANKL further diminished parameters of formation in oim-RANKL-cKO. Our results indicate that osteocytes contribute significantly to the low bone mass observed in OI and the effect of loss of RANKL from these cells is similar to its systemic inhibition.